2014
DOI: 10.1089/ars.2014.6072
|View full text |Cite
|
Sign up to set email alerts
|

May the Thyroid Gland and Thyroperoxidase Participate in Nitrosylation of Serum Proteins and Sporadic Parkinson's Disease?

Abstract: The research group has detected nitrosative stress and a singular version of nitrosylated serum a-synuclein in serum of Parkinson's disease (PD) patients. Dysfunction of the thyroid gland has been proposed to be linked to this disease. The aim of the study was to know if the thyroid gland is involved in idiopathic PD and nitrosative stress. We studied 50 patients (early and advanced disease patients), 35 controls, and 6 subjects with thyroidectomy. Clinical characteristics, serum thyroperoxidase levels, and 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…They further verified the possible neurological differences between PD and non-PD patients as being related to thyroid autoimmunity and function. Recently, increasing data have confirmed that hypo- and hyperthyroidism are more prevalent in PD patients than in normal controls because thyroperoxidase can influence PD nitrosative stress as well as serum α-syn nitrosylation ( 98 ). Likewise, in the last year, Bartkiewicz et al confirmed that patients suffering bullous pemphigoid (BP), an autoimmune blistering dermatosis that occurs in the elderly, were more likely to suffer from neurological and psychiatric diseases, particularly prior to the diagnosis of BP ( 99 ).…”
Section: Other Autoimmune Diseases Combined With Pdmentioning
confidence: 99%
“…They further verified the possible neurological differences between PD and non-PD patients as being related to thyroid autoimmunity and function. Recently, increasing data have confirmed that hypo- and hyperthyroidism are more prevalent in PD patients than in normal controls because thyroperoxidase can influence PD nitrosative stress as well as serum α-syn nitrosylation ( 98 ). Likewise, in the last year, Bartkiewicz et al confirmed that patients suffering bullous pemphigoid (BP), an autoimmune blistering dermatosis that occurs in the elderly, were more likely to suffer from neurological and psychiatric diseases, particularly prior to the diagnosis of BP ( 99 ).…”
Section: Other Autoimmune Diseases Combined With Pdmentioning
confidence: 99%
“…Available research does not make it possible to conclusively interpret S-nitrosothiols as oxidative stress marker. However, in some papers, reduced levels of nitrosylation were demonstrated in patients with such neurodegenerative diseases as Alzheimer's disease, Parkinson's disease or Huntington's disease [31,32]. The adverse effect of S-nitrosothiols on reproduction cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…They visualized tiny α-syn was rich in the cortex of neurodegenerative diseases patients (Schulz-Schaeffer, 2010 ). Posttranslational modifications including phosphorylation, nitrosylation and ubiquitination of α-syn have been found to play roles in α-syn accumulation and aggregation (Fernández et al, 2014 ; Alexopoulou et al, 2016 ; Kumar P. et al, 2017 ; Kumar R. et al, 2017 ; Zhong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%